HUMANITARIAN CARE AND THE ENDS OF LIFE: The Politics of Aging and Dying in a Palestinian Refugee Camp. (February 2017) - FELDMAN, ILANA
ABSTRACT: What is it to live as a refugee over the long term? One thing that it can mean— and in the Palestinian case of nearly seventy years of displacement, what it necessarily has meant for many people—is to die as a refugee. This essay explores the consequences of the ways in which humanitarian work has been compelled to take up the end of life as a humanitarian concern. Drawing on fieldwork in the Burj al Barajneh Palestinian refugee camp in Lebanon, it explores care for the aging and dying as a setting in which key aspects of the social world produced through humanitarianism are brought into existence and view. The problems of the end of life introduce additional challenges into the conundrums of long‐term humanitarianism, occurring at the intersection of humanitarian practice and Palestinian experience. With the questions of services for the aging and dying foregrounded, the possibility of the future becomes a site of confrontation among, and within, providers and recipients. Often, this future appears to be foreclosed.